The Effect of Work Discipline and Organizational Culture on Employee Performance: Study at a Government Agency in Bandung Regency - Ernita Rahmawati; Adhie Fasha Nurhadian (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
This study aims to comprehensively examine and evaluate the work discipline, organizational culture, and performance of employees at a government agency located in Bandung Regency. Additionally, the research aims to determine the degree of influence that work discipline and organizational culture has on employee performance within the government above agency. The author employed a research methodology that falls under descriptive and verificative research. This approach was utilized to determine the significant relationship between the variables under investigation, ultimately leading to conclusions that accurately describe the research object. The participants in this study consisted of 32 employees who were selected as respondents from a government agency located in Bandung Regency. The findings of this research demonstrate that (1) Work Discipline exhibits a positive and statistically significant impact on Employee Performance, and (2) Organizational Culture also displays a positive and statistically significant influence on Employee Performance. The relationship between work discipline and organizational culture has been found to have a positive and statistically significant impact on employee performance.